Exiled Writer In Migrant Literature - Soghomonyan, Amalya (Տիգրան Մեծ)
The purpose of this paper is to reveal the phenomena of the exiled writer in migrant literature. The perceptions of homesickness, identity, belonging, multiculturalism, otherness, and exile help us to highlight a number of psychological realities that the exiled writer faces becoming a migrant. With the help of mythological, sociological and psychological categories, we tried to open hidden layers of migration. Migrant literature is individual, subjective, diverse, but the causes that make writer become migrant are sometimes similar.
Keywords: Migrant literature